Constraint Estimation Schemes For Semi-Elliptical Surface Cracks Under Tensile And Bending Loads - Latiff, Rizman Hariz Abdul (2017)
A three-dimensional constraint estimation scheme was examined for surface cracked plates with semi-elliptical surface cracks under tensile and bending loads. Detailed finite element models were developed to elucidate the crack tip constraint along the crack front of a semi-elliptical surface crack. The finite element models were characterized with a non-hardening elastic-perfectly plastic material with a hardening exponent of